Report on proposed upgrading new interior design of lobby and business center for Fair Park Hotel at No 85 Jalan Kamaruddin Isa, 31400 Ipoh, Perak. / Muhamad Najib Romli - Romli, Muhamad Najib (Faculty of Architecture, Planning and Surveying, 2010)
A final year student of diploma course in Interior Design is required to prepare one final year project Its compulsory requirements to get a scroll of diploma. The selection of the project must be related to current issues to help student succeed. The knowledge and skills are required along the process of design works which include research, case study, interviewing, designing a proposal, submission by stages, create session, preparing art work, preparing presentation drawings, design development and final presentation. The client of this project is Fair Park Hotel. Therefore, the project is propose to design a hotel which may interest and fulfil the aspect of design and practicality for user in the mean time give an aspiration to the proprietor of the hotel, and owner of the Fair Park Hotel who manage the hotel. The research will involved research methodology such as interview, observation, internet and side references conducted on the products and designing the boutique will be gathered with others related information and details which work as guideline to prepare this project. The objective is to create a very well boutique with concept and style that related to this product and give the desire images that needed to enhance the interest of the proprietor.